Patient‐reported outcomes after 3‐dimensional conformal, intensity‐modulated, or proton beam radiotherapy for localized prostate cancer123. Issue 9 (22nd February 2013) - Gray, Phillip J.; Paly, Jonathan J.; Yeap, Beow Y.; Sanda, Martin G.; Sandler, Howard. M.; Michalski, Jeff M.; Talcott, James A.; Coen, John J.; Hamstra, Daniel A.; Shipley, William U.; Hahn, Stephen M.; Zietman, Anthony L.; et al.
Abstract: BACKGROUND: Recent studies have suggested differing toxicity patterns for patients with prostate cancer who receive treatment with 3‐dimensional conformal radiotherapy (3DCRT), intensity‐modulated radiotherapy (IMRT), or proton beam therapy (PBT). METHODS: The authors reviewed patient‐reported outcomes data collected prospectively using validated instruments that assessed bowel and urinary quality of life (QOL) for patients with localized prostate cancer who received 3DCRT (n = 123), IMRT (n = 153) or PBT (n = 95). Clinically meaningful differences in mean QOL scores were defined as those exceeding half the standard deviation of the baseline mean value. Changes from baseline were compared within groups at the first post‐treatment follow‐up (2‐3 months from the start of treatment) and at 12 months and 24 months. RESULTS: At the first post‐treatment follow‐up, patients who received 3DCRT and IMRT, but not those who received PBT, reported a clinically meaningful decrement in bowel QOL. At 12 months and 24 months, all 3 cohorts reported clinically meaningful decrements in bowel QOL. Patients who received IMRT reported clinically meaningful decrements in the domains of urinary irritation/obstruction and incontinence at the first post‐treatment follow‐up. At 12 months, patients who received PBT, but not those who received IMRT or 3DCRT, reported a clinically meaningful decrement in the urinary irritation/obstruction domain. At 24 months, none of the 3 cohorts reported clinically meaningful changes in urinary QOL. CONCLUSIONS: Patients who received 3DCRT, IMRT, or PBT reported distinct patterns of treatment‐related QOL. Although the timing of toxicity varied between the cohorts, patients reported similar modest QOL decrements in the bowel domain and minimal QOL decrements in the urinary domains at 24 months. Prospective randomized trials are needed to further examine these differences. Cancer 2013. © 2013 American Cancer Society. Abstract : Prostate cancer patients who receive 3‐dimensional conformal radiotherapy, intensity‐modulated radiotherapy, or proton beam therapy report distinct patterns of treatment‐related quality of life. Although the timing of toxicity varies between cohorts, patients report similar modest quality‐of‐life decrements in the bowel domain and minimal QOL decrements in the urinary domains at 24 months.